Role of Serum Ferritin, Vitamin D Status, and C-Reactive Protein in Nonalcoholic Fatty Liver Disease: A Case-control Study - Mary Chandrika Anton; B Shanthi; Vasudevan Elumalai; K Sumathi (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Nonalcoholic Fatty Liver Disease (NAFLD) is an increasingly prevalent metabolic liver disorder associated with chronic low-grade inflammation. Altered iron metabolism, Vitamin D deficiency, and systemic inflammatory markers have been implicated in its pathogenesis; however, their relationship with disease severity remains incompletely understood. Aim: To evaluate the association of serum ferritin, Vitamin D status, and C-Reactive Protein (CRP) with the presence and severity of NAFLD. Materials and Methods: This hospital-based case-control study was conducted at the Department of Biochemistry, Sree Balaji Medical College and Hospital, Chennai, Tamil Nadu, India, from January 2023 to December 2023. A total of 200 participants were enrolled, including 100 NAFLD patients diagnosed by clinical, biochemical, and ultrasonographic criteria and 100 age- and gender-matched healthy controls. Serum ferritin, 25-hydroxyvitamin D, and CRP levels were estimated using standard laboratory methods. Data were analysed using Statistical Package for Social Sciences (SPSS) version 26.0. Normality was assessed using the Shapiro-Wilk test. MannWhitney U test and Chi-square/Fisher’s-exact tests were used for group comparisons, while Spearman’s rank correlation was used to assess associations with NAFLD severity. Results: The mean age of NAFLD patients was 32.27±3.99 years, and that of controls was 31.46±4.19 years, with equal gender distribution in both groups (50 males and 50 females). NAFLD patients had significantly higher median serum ferritin [183.0 (148.0-254.75) vs 145.0 (97.75-236.25) ng/mL; p=0.0001] and CRP levels [6.5 (5.0-9.5) vs 1.5 (0.8-2.0) mg/L; p